(untitled) (Revista científica Olimpia, 2026)
The thinking of Commander-in-Chief Fidel Castro Ruz encompassed multiple spheres of human knowledge, a characteristic that defined him throughout his life. This led him to pursue self-directed learning in diverse fields and to make significant contributions to sciences such as economics, to which he devoted special attention, even before 1959. A distinctive feature of Fidel Castro’s contributions to the analysis of the economic and social problems present in his revolutionary work was that, although he did not set out to develop a specific economic philosophy, it developed organically from a purely academic study of the complex realities of building socialism in Cuba and the contemporary world. This article aims to analyze Fidel Castro’s economic thought in relation to the social relations of production, and especially to the relations of distribution. The study of distribution according to labor under current conditions reveals the existence of various problems that limit its proper implementation. This work employs the universal theoretical method of dialectical materialism and its specific methods: analysis and synthesis, the unity of the logical and the historical, and qualitative and quantitative analysis of economic phenomena.